An Overview of STAKCERT Framework in Confronting Worms Attack - Madihah Mohd Saudi; Cullen, AJ; Woodward, ME; Hamid, HA; Abhalim, AH (IEEE, 2024)
A procedure is one of the most important elements that should be emphasized when handling any incident related with the cyber world. It is easily forgotten by many organizations, IT administrator and users, especially when dealing with the worms attack. Using the incident response methodology as the basis to build up the STAKCERT framework, the researchers have proposed this novel framework which helps to increase the efficiency in handling worm incident, thus facilitate the process of responding to the worm incident The STAKCERT framework consists of 2 phases where in phase 1, a novel standard operating procedure in worm detection and analysis have been introduced. In phase 2 of the framework, the worm isolation procedure is inspired by apoptosis. Apoptosis is also known as cell programmed death borrowed from the biology term.